Utilização da Psicanálise nos Cuidados Paliativos - SCOPING REVIEW - Isabella Batista Jardim (2023)
Context: With the expansion of psychoanalysis to different institutions, it is urgent for professionals to adapt to the reality that is presented to them, so that psychoanalytic concepts and the listening of unconscious can be done, detached from walls and pre-established protocols. Palliative care is one of the fields in which psychoanalysis is increasingly inserted, since providing these listening spaces is also necessary in the hospital context. Throughout this work, the particularities and challenges of performing psychoanalysis in palliative care will be presented. Goals: Explore existing studies regarding the use of psychoanalysis in Palliative Care. Methods: Scoping review based on the principles recommended by the Joanna Briggs Institute. The databases consulted were Scopus, Medline (Pubmed), Web of Knowledge (ISI) and PEPSIC, using the following key concepts: palliative care AND psychoanalysis. The research took place on August 8, 2023, at 9:00 am, with no time horizon being defined. From the total of 70 articles found, 11 met the previously designated selection criteria and were considered in the presented review. Results: The research carried out resulted in the selection of 11 articles included in the review. Aspects regarding the use of psychoanalysis in palliative care were identified, such as the need for adaptation by the psychoanalyst to the work setting, the importance of valuing subjectivity with the team and consequently listening to patients and families, the psychoanalyst's responsibility in which concerns the consolidation of their place in the team, the use of ethics and psychoanalytic concepts in order to promote listening to the unconscious. Conclusions: This review shows that there are many challenges faced by psychoanalysts when working in palliative care. However, it also demonstrates that the correct handling of situations and demands can contribute to the consolidation of the psychoanalyst's place in this space, so that listening to the subject can be promoted, regardless of the setting in which this listening takes place. After all, wherever there is someone willing to listen, there will be an unconscious subject willing to speak. Psychoanalytic listening is not and should not be limited to the walls of the office, but must reach everyone. Keywords: Palliative Care; Psychoanalysis.